2021
DOI: 10.1113/ep089272
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training decreases whole‐body and tissue iron storage in adults with obesity

Abstract: The regulation of iron storage is crucial to human health, because both excess and deficient iron storage have adverse consequences. Recent studies suggest altered iron storage in adults with obesity, with increased iron accumulation in their liver and skeletal muscle. Exercise training increases iron use for processes such as red blood cell production and can lower whole-body iron stores in humans. However, the effects of exercise training on liver and muscle iron stores in adults with obesity have not been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A meta-analysis of sixteen studies showed that hepcidin increased with both aerobic and resistance exercise [ 129 ]. In adults with obesity, a 12 week exercise intervention consisting of either high-intensity or moderate-intensity interval training led to a decrease in whole body iron stores (as indicated by decreased ferritin) and reduced skeletal muscle iron stores, with a non-significant reduction in hepatic iron [ 130 ].…”
Section: Iron and Insulin Resistancementioning
confidence: 99%
“…A meta-analysis of sixteen studies showed that hepcidin increased with both aerobic and resistance exercise [ 129 ]. In adults with obesity, a 12 week exercise intervention consisting of either high-intensity or moderate-intensity interval training led to a decrease in whole body iron stores (as indicated by decreased ferritin) and reduced skeletal muscle iron stores, with a non-significant reduction in hepatic iron [ 130 ].…”
Section: Iron and Insulin Resistancementioning
confidence: 99%
“…In that study, no basal differences were seen between groups in WAT, whereas the expression of FTL in visceral adipose tissue was increased in the heavily obese group, suggesting depot-specific differences in iron metabolism ( 73 ). One study recently explored the effects of exercise training on tissue iron homeostasis in obese men and women and found that HIIT decreased protein ferritin levels in serum, skeletal muscle, and liver ( 74 ). In line with existing evidence, we found that HIIT decreased serum ferritin and iron, but unexpectedly, HIIT increased the protein levels of the ferritin subunits in scWAT.…”
Section: Discussionmentioning
confidence: 99%
“…Waist circumference is a simple evaluation index for evaluating visceral fat, and waist circumference reduction is of great significance for reducing the risk of cardiovascular disease (29). The highintensity short-interval HIIT program can withstand exercise intensity above 100% MAS (30). This program has a significant effect on reducing the waist circumference of overweight and obese adolescents, which may be due to the higher sensitivity of human body fat to exercise intensity.…”
Section: Discussionmentioning
confidence: 99%